Pendidikan Anak Dalam Keluarga - Mimpira Haryono; Rohayu Fadilla; Siti nurjana; Dela Puspita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Parental strategies in developing disciplined character in early childhood, Early Childhood Teacher Education Study Program, University of Bengkulu. This study aims to analyze parental strategies in instilling disciplined character in early childhood. This study uses a qualitative approach with observation, interview, and documentation methods to collect data. The subjects of the study were parents, who were selected as key informants. The results of the study showed that parents implemented various learning strategies to instill discipline, including direct and indirect learning strategies. Through the direct learning strategy, the result was that children could understand the rules and develop good disciplined behavior, and the indirect learning strategy resulted in children being able to model positive behavior from parents.